Stable isotopes of gypsum hydration water in recent playa-lake sediments: implications for paleoclimate reconstructions - Jorge Cañada-Pasadas; Fernando Gázquez; Lucía Martegani; Claudia Voigt; Antonio García-Alix; Gonzalo Jiménez-Moreno; Miguel Rodríguez-Rodríguez (Geogaceta)
We investigate the oxygen and hydrogen stable isotopes of hydration water in gypsum (CaSO4·2H2O) from surface sediment of Laguna de la Ratosa playa-lake (northern Málaga Province, Spain). We aim to enhance the understanding of how lacustrine gypsum from playa-lakes can be used for paleoclimate reconstruction. Gypsum samples were collected at 30-meter intervals along a transect from the shore to the depocenter of the lake. Comparison of δ18O and δ2H values of gypsum hydration water with the modern seasonal isotope variability of lake water point to gypsum formation in spring and early summer, before complete desiccation of the lake. An increasing trend in the δ18O and δ2H values of gypsum hydration water, by ~1,5 and ~15‰, respectively, is observed from the shore to the depocenter. This indicates that coeval gypsum formed in different parts of the lakebed record slightly different isotopic values of the lake water during precipitation. This spatial variability should be considered when interpreting stable isotope series of gypsum hydration water from ephemeral lake sediments.